EFFECT OF BIOFERTILLIZER PRODUCED FROM LOCAL ISOLATES OF Pseudomonas putida AND Pseudomonas fluorescens ON SOME SOIL CHARACTERISTICS AND YIELD OF WHEAT (Triticum aestivum L) B -CONCENTRATIONS OF SOME NUTRIENTS IN SOIL - & et al., Abed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Field experiment was conducted by using randomized complete block design with three replicates to evaluate the effect of biofertilizer of   Pseudomonas putida and Pseudomonas  fluorescens alone or together with peatmoss or bentonite as carriers interacted with four mineral fertilizer levels (zero , 25% , 50% , and 75%) of the recommended level on the growth and yield of wheat (Alrasheed varity) , tow control treatments were used ,the first with out of biofertilizer and  mineral fertilizer and the second included the addition of the recommended level (100%) of mineral fertilizer  Significant ,effect of the addition of biofertilizer  supplemented with    mineral fertilizer  for concentrations N,P,K,Fe and Zn , the N was 59.63mg.N.Kg-1 soil in B2C1M2 which increased by 322.9% over the first control treatment, 49.33 63mg.P.Kg-1 soil in B1C2M3 which increased by 252.3% over the first control treatment , 295mg.K.Kg-1 soil in B3C2M3 which increased by 118.5% over the first control treatment, 10.07mg.Fe.Kg-1 soil in B2C1M0 which increased by 108.4% over the first control treatment, 1.6163mg.Zn.Kg-1 soil in B1C2M2 which increased by 108.4% over the first control treatment .